Numerical analysis on static load capacity of prestressed concrete sleepers under hypothetical bearing pressure distribution - Wan Abdul Rashid, Wan Azlan (2012)
Prestressed concrete sleepers are currently designed based on permissible stresses concepts resulting from quasi-static wheel loads. It was designed to exceed the mean working load to avoid loss of bond in the prestressing due to cracking of the concrete sleepers. These loads allow for static response of the sleeper due to the mechanism of vertical load transfer between the rail and sleeper as well as the sleeper and ballast interaction. In practice, the designer apply uniform pressure distribution beneath each rail seat which is dependent on the track gauge and sleeper length as stipulated in many design standards. Applying uniform pressure distribution beneath each rail seat may not be necessarily applicable to all in-situ sleepers as the contact pressure distribution between sleepers and ballast is mainly influenced by the cumulative effect of the traffic loading at various speeds over a period of time as well as the quality of ballast maintenance. A significant amount of research has been conducted by researchers worldwide over the century in postulating a set of hypothetical contact pressure distribution on the sleeper-ballast interaction. This leads to predicament as to whether the designed sleepers under the assumption of uniform contact pressure distribution had the adequate static load capacity to withstand the designed vertical loading but under different contact pressure distribution pattern. To solve this predicament, numerical analysis using commercially available finite element package, LUSAS, is carried out and comparison is made with the experimental test results in validating the finite element model. The numerical analysis will be useful in predicting the maximum vertical loading prior to the cracking of the sleeper under various hypothetical contact pressure distribution patterns. From numerical analysis, prestressed concrete sleeper that is placed on ballast has reserve strength in static load capacity with a factor between 2.2 and 2.4 of the positive rail seat test load at crack initiation.